(untitled) (Per Musi, 2012)
Exploratory research with 40 musicians on the risk of osteomuscular disorders related to work, the furniture used by musicians and the postures adopted during rehearsals of the Orquestra Filarmônica do Espírito Santo (OFES) in Brazil. The postural assessment used the visual REBA (Rapid Entire Body Assessment) and the chairs and music stands have been evaluated following ergonomic criteria. The results indicate a postural inadequacy of the musicians during rehearsals, as well as irregularity of the furniture used, pointing to the need of immediate physiotherapic action for both rehabilitation and for injury prevention.